2019
DOI: 10.1002/mgg3.506
|View full text |Cite
|
Sign up to set email alerts
|

The promising role of PAX1 (aliases: HUP48, OFC2) gene methylation in cancer screening

Abstract: Background Paired‐box gene 1 ( PAX1 ), a member of the PAX family, plays a role in pattern formation during embryogenesis, and might be essential for development of the vertebral column. Methods PAX1 is silenced by methylation in several cancers and is considered a tumor suppressor gene. Our previous studies reported PAX1 as hypermethylated in cervical cancer tissues, thereby suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…In previous studies and our work, 14 20 hypermethylation of RASSF1A, HIST1H4F, Septin 9, and PAX1 has been found in tissue samples from patients with EC and other malignancies including colorectal cancer, and cervical cancer. However, the feasibility of DNA methylation testing in cervical Pap brush samples and its value for EC detection remains largely undetermined.…”
Section: Introductionsupporting
confidence: 66%
“…In previous studies and our work, 14 20 hypermethylation of RASSF1A, HIST1H4F, Septin 9, and PAX1 has been found in tissue samples from patients with EC and other malignancies including colorectal cancer, and cervical cancer. However, the feasibility of DNA methylation testing in cervical Pap brush samples and its value for EC detection remains largely undetermined.…”
Section: Introductionsupporting
confidence: 66%
“…Mersakova et al (2018) and Rong et al (2019) have recently shown that CADM1 is a potential biomarker for cervical cancer. There was a significant difference in the promoter Kan et al, 2014;Lai et al, 2014;Kong et al, 2015;Nikolaidis et al, 2015;Xu et al, 2015Xu et al, , 2018Chen et al, 2016;Liou et al, 2016;Huang et al, 2017;Fang et al, Lee et al, 2006;Yeon et al, 2018 methylation of plasma CADM1 and its D-dimer between healthy individuals and those with cervical cancer. Combining these factors to predict metastasis revealed high specificity (90.5%) and sensitivity (80.4%) (Rong et al, 2019).…”
Section: Dna Methylation In the Early Diagnosis Of Cervical Cancermentioning
confidence: 97%
“…Hypermethylated PAX1 is important in cancer progression (Huang et al, 2017) that functions in regulating cellular differentiation and proliferation (Fang et al, 2019). PAX1 can be used to detect cervical squamous cell carcinoma (CSCC) in 121 patients from eastern China with 80.9, 83.7, and 79.0% accuracy, specificity, and sensitivity, respectively (Xu et al, 2018).…”
Section: Diagnostic Dna Methylation Biomarkers For Hpv-positive and Nmentioning
confidence: 99%
“…It has been reported that the disruption between kinases and phosphatases caused by PAX1 methylation is involved in cervical carcinogenesis ( 33 ). An increasing number of studies have confirmed PAX1 methylation as a promising biomarker for cervical cancer based on its ability to discriminate between high‐grade cervical lesions and normal tissues, resulting in a reduced necessity for colposcopy referral and biopsy ( 9 , 10 , 34 ). The current study demonstrated that the ΔCp PAX1 level of CIN3 determined by CDB was lower than that of CIN2 and the ΔCp PAX1 level of ESCC was lower than that of both CIN2 and CIN3.…”
Section: Discussionmentioning
confidence: 99%